2002
DOI: 10.1093/emboj/cdf342
|View full text |Cite
|
Sign up to set email alerts
|

Mapping histone fold TAFs within yeast TFIID

Abstract: The transcription factor TFIID is a large multiprotein complex, composed of the TATA box-binding protein (TBP) and 14 TBP-associated factors (TAFs), which plays a key role in the regulation of gene expression by RNA polymerase II. The three-dimensional structure of yeast (y) TFIID, determined at~3 nm resolution by electron microscopy and image analysis, resembles a molecular clamp formed by three major lobes connected by thin linking domains. The yTFIID is structurally similar to the human factor although the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
106
0
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(125 citation statements)
references
References 38 publications
16
106
0
3
Order By: Relevance
“…These experiments showed that not all the TFIID-specific Tafps coprecipitated with Taf1p-region 4: for example, Taf1p, Taf2p, and Taf8p were not detected in these immunoprecipitates. We also note that no such dimer has yet been detected for yeast TFIID by co-IP (14,62), TFIID molecular sizing (62), or electron microscopy (39,40).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…These experiments showed that not all the TFIID-specific Tafps coprecipitated with Taf1p-region 4: for example, Taf1p, Taf2p, and Taf8p were not detected in these immunoprecipitates. We also note that no such dimer has yet been detected for yeast TFIID by co-IP (14,62), TFIID molecular sizing (62), or electron microscopy (39,40).…”
Section: Discussionmentioning
confidence: 88%
“…24,2004 SCAFFOLD FUNCTION OF Taf1p IN TFIID ASSEMBLY 4937 TFIID complex has emerged. New TFIID-specific Tafps have been identified (33,34,60,65,75), novel Tafp-Tafp interactions have been described (22,23,63,66,81), and low-resolution three-dimensional structures of the TFIID complex have been determined (2,11,39,40,48). In this study, we have performed a comprehensive analysis of all the TFIID components associated with Taf1p using co-IP assays and our family of Taf1p deletion mutants that encompass the entire TAF1 ORF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 1A) [6]. L'utilisation d'anticorps a permis de positionner les différents TAF dans la structure de TFIID [7]. Les positions de TBP et de TAF2, tous deux impliqués dans la liaison avec le promoteur, ainsi que celle de l'extrémité amino-terminale de TAF1, qui comprend les motifs inhibiteurs TAND, ont été déterminées ( Figure 1A).…”
Section: Le Coactivateur Tfiidunclassified